2004
DOI: 10.1002/art.11485
|View full text |Cite
|
Sign up to set email alerts
|

Selective cleavage of nucleolar autoantigen B23 by granzyme B in differentiated vascular smooth muscle cells: Insights into the association of specific autoantibodies with distinct disease phenotypes

Abstract: Objective. To investigate the association of specific autoantibodies with distinct disease phenotypes. The association of autoantibodies to nucleophosmin/ B23 with pulmonary hypertension in scleroderma, and the susceptibility of autoantigens to cleavage by granzyme B (GB), provided a focus for these studies.Methods. Intact cells were subjected to cytotoxic lymphocyte granule-induced death, and the susceptibility of autoantigens to cleavage by GB was addressed by immunoblotting and/or by a novel immunofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Among those reported are various MMPs (17)(18)(19) and plasmin reductase (20,21). Granzyme B, a serine protease found in T cell granules, is strikingly associated with cleavage of autoantigens targeted by autoantibodies in patients with SSc (33,56). In agreement with this hypothesis, we demonstrated that both granzyme B and the full granule content could indeed cleave plasminogen into varioussized fragments containing angiostatin K [1][2][3] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Among those reported are various MMPs (17)(18)(19) and plasmin reductase (20,21). Granzyme B, a serine protease found in T cell granules, is strikingly associated with cleavage of autoantigens targeted by autoantibodies in patients with SSc (33,56). In agreement with this hypothesis, we demonstrated that both granzyme B and the full granule content could indeed cleave plasminogen into varioussized fragments containing angiostatin K [1][2][3] .…”
Section: Discussionsupporting
confidence: 63%
“…Although several proteases can potentially cleave plasminogen in a manner that would lead to angiostatin production, granzyme B is a particularly interesting candidate given its high levels in the peripheral blood cells of some patients with SSc (32,33). To determine whether granzyme B can cleave plasminogen, SSc and control plasma samples were allowed to interact with granzyme B or the entire granule content (the source of granzyme B) in vitro ( Figure 2C).…”
Section: Angiogenesis Inhibitors In Systemic Sclerosis 3451mentioning
confidence: 99%
“…We cannot exclude the possibility that gzmB directly processes c-gelsolin in specific subtypes of cells. For example, the B23 autoantigen is most susceptible to cleavage by gzmB in differentiated smooth muscle cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies against B23, a cleavage product of a nuclear protein produced by the T cell enzyme granzyme B, can distinguish the subset of patients with scleroderma who also have PAH from patients with scleroderma without PAH (111). The mechanistic significance of this biomarker is not known.…”
Section: The Proinflammatory State Of the Vessel Wall And Pahmentioning
confidence: 99%